Development of health educational action for individuals with heart failure: Experience report (Research, Society and Development, 2025)
Objective: To report the experience of a nurse resident in cardiovascular health, regarding the construction of an application project proposal in an outpatient environment for different cardiological clinics evaluated in individuals affected by heart failure, in order to improve quality of life. Methods: Experience report, with an observational, analytical approach, descriptive and qualitative in nature, following the steps of a methodological, applied research, in order to characterize itself as a process of construction and development of a product and improvement actions regarding health education and adherence of individuals to the proposed health therapies. Results and discussion: Creation of a research project based on scientific aspects, which allows the evaluation of different spheres associated with the individual affected by heart failure. Variables were defined to be evaluated and measured using validated scientific instruments, being defined as outcome and other variables. Conclusion: Individuals affected by heart failure have limitations in their quality of life, thus nursing plays an active role in the development of educational health actions, which promote greater autonomy and increase therapeutic adherence of these individuals.